Review of Letra y Metralla - Ortega Reyna, Jaime (2024)
This review addresses the book by North American scholar Sophi Esch on Central American and Mexican literature and music produced in themidst of events involving the use of violence. Using a variety of registers, the author observes the processes of agency, linked to notions such as masculinity or independence. The book can be considered a cultural history of social productions, which start from varied contingents and are located from diverse places of enunciation. Review Letra y Metralla. Cultura y política durante los periodos de conflictos armados en México y Centroamérica (1910-1920), Ciudad de México, Bonilla Artiga Editores, 2022, of has 350 pages and ISBN: 978-607-8838-09-7